Mechanical Properties of Rock–Coal–Rock Composites at Different Inclined Coal Seam Thicknesses - Ma, Bo; Wang, Feng; Liu, Hongyang; Yin, Dawei; Xia, Zhiguo (Frontiers in Physics, 2022)
A comprehensive understanding of the mechanical properties of coal and rock sections is necessary for interpreting the deformation and failure modes of such underground sections and for evaluating the potential dynamic hazards. However, most studies have focused on horizontal coal–rock composites and the mechanical properties of inclined coal–rock composites have not been considered. To explore the influence of different confining pressures and inclined coal seam thicknesses on the mechanical properties and failure characteristics of rock–coal–rock (RCR) composites, a numerical model based on the particle flow code was used to perform simulations on five inclined RCR composites at different confining pressures. The results show that the mechanical properties and failure characteristics of the RCR composites are affected considerably by the inclined coal seam thickness and the confining pressure. (1) When the inclined coal seam thickness is constant, the elasticity modulus of the inclined RCR composite increases nonlinearly with the confining pressure at first, and then remains constant. At the same confining pressure, the elasticity modulus of the inclined RCR composite decreases nonlinearly with the inclined coal seam thickness. (2) When the confining pressure is constant, the peak stress of the inclined RCR composite decreases with the increase of the inclined coal seam thickness. When the inclined coal seam thickness is constant, the peak stress increases with the confining pressure. (3) As the inclined coal seam thickness increases, the peak strain of the inclined RCR composite first decreases rapidly, and then remains constant when there is no confining pressure. When the confining pressure is between 5 and 20 MPa, the peak strain of the inclined RCR composite gradually increases. (4) In the absence of confining pressure, there are few microcracks in the rock at an inclined coal seam thickness of 10 mm, whereas all the other cracks are in the coal section. When the confining pressure ranges between 5 and 20 MPa, the failure modes of the RCR composite can be divided into Y- and X- types.